Investigating the factors affecting whistle-blowing by employees in the hospital - Fatemeh Mohammadkhani Ghiasvand; Masoumeh Abbasabadi Arab; Habibollah Taherpour Kalantari; Hossein Alipour (Tehran University of Medical Sciences, 2022)
Background: The occurrence of all kinds of errors and mistakes imposes many costs on the hospital and society. Whistleblowing and error reporting plays an essential role in preventing and reducing errors, but the rate of error reporting in hospitals is low. This research was conducted in order to investigate the effect of selected individual factors on whistleblowing of hospital employees. Materials: The research was conducted as a descriptive correlational study. 229 nursing and para clinic staff of a hospital in Tehran were selected by random sampling. A standard questionnaire with 69 items from valid questionnaires of selected factors, including organizational commitment, source of control, moral judgment, altruism, individual's attitude towards whistleblowing and intention to whistleblowing was collected and its validity and reliability were confirmed. The method of data analysis was confirmatory factor analysis and SPSS and Amos software were used as well. Results: The variables of organizational commitment, altruism and individual's attitude towards whistleblowing have an effect on the intention of whistleblowing, and moral judgment and source of control have no effect on the intention of whistleblowing. Also, individual variables such as age, gender, and work experience did not have a significant effect on the intention to blow the whistle. Conclusion: Strengthening organizational commitment, altruism of employees and the positive attitude of the individual toward whistle-blowing play an important role in improving error reporting. Hospital management methods can strengthen or weaken these factors. Participatory management style, job empowerment, supporting and creating a safe environment for reporting, promoting employees' ethical and professional principles,  and learning and sharing medical errors are effective measures in promoting whistle-blowing.